More answers

They can both divide by 4.

4(2y - 3)

Q: How do you factor 8y -12?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

16y^2(8y)=0? Factor out an 8y to give you 8y(2y(2))=0 Use order of operations to give you 8y(4y)=0 Distribute to give you 32y=0 and ultimately the answer will be 0 If there is a missing plus or minus operator between 16y2 and the 8y, then it can be factorised by taking out common factors: 16y2 ± 8y = 0 ⇒ 8y(2y ± 1) = 0

Not sure which you mean, take your pick: (8y)3+27=(8y+3)((8y)2-3*(8y)+9)=(8y+3)(64y2-24y+9); or 8y3+27=(2y+3)(4y2-6y+9)

8y + 7y = 15ySo [ 8y + 9 + 7y ] = 15y + 9If you want to get fancy and factor that expression, it's 3(5y + 3) .

4y + 8y = 12y 4y - 8y = -4y 4y x 8y = 32y2 4y/8y = 1/2

y2 +8y + 16 = 0 can factor to (y+4) (y+4) = 0 so y+4 = 0 so y = -4

Related questions

The only thing you can do to this is factor it... (4x + 8y)(4x - 8y)

(5 - 11y - 12) + 8y = 5 - 11y - 12 + 8y = ( - 7 - 3y )

16y^2(8y)=0? Factor out an 8y to give you 8y(2y(2))=0 Use order of operations to give you 8y(4y)=0 Distribute to give you 32y=0 and ultimately the answer will be 0 If there is a missing plus or minus operator between 16y2 and the 8y, then it can be factorised by taking out common factors: 16y2 ± 8y = 0 ⇒ 8y(2y ± 1) = 0

Not sure which you mean, take your pick: (8y)3+27=(8y+3)((8y)2-3*(8y)+9)=(8y+3)(64y2-24y+9); or 8y3+27=(2y+3)(4y2-6y+9)

6x+8y = 12 8y = -6x+12 Divide all terms by 8:- y = -0.75x+1.5 which is now in slope intercept form

8(y - 1)

8(y-9)

8y + 7y = 15ySo [ 8y + 9 + 7y ] = 15y + 9If you want to get fancy and factor that expression, it's 3(5y + 3) .

( 2xy - 4x ) + ( 8y - 16)2 ( xy - 2x ) + 2 ( 4y - 8 ) Answer

2(8y + 1)

4(2y + 3)

Need to put in function form. Y =mX + c 6X + 8Y = 12 8Y = - 6X + 12 Y = - 3/4X + 3/2 ----------------------- read off function m = - 3/4 ---------------------slope